Providing an e-cigarette starter kit for smoking cessation and reduction as adjunct to usual care to smokers with a mental health condition: findings from the ESCAPE feasibility study - Dimitra Kale; Emma Beard; Anna-Marie Marshall; Jodi Pervin; Qi Wu; Elena Ratschen; Lion Shahab (BMC Psychiatry)
Abstract Background Smoking rates in the UK have declined steadily over the past decades, masking considerable inequalities, as little change has been observed among people with a mental health condition. This trial sought to assess the feasibility and acceptability of supplying an electronic cigarette (e-cigarette) starter kit for smoking cessation as an adjunct to usual care for smoking cessation, to smokers with a mental health condition treated in the community, to inform a future effectiveness trial. Methods This randomised controlled feasibility trial, conducted March-December 2022, compared the intervention (e-cigarette starter kit with a corresponding information leaflet and demonstration with Very Brief Advice) with a ‘usual care’ control at 1-month follow-up. Participants were ≥ 18 years, receiving treatment for any mental health condition in primary or secondary care in three Mental Health Trusts in Yorkshire and one in London, UK. They were also willing to address their smoking through either cessation or reduction of cigarette consumption. The agreed primary outcome measure was feasibility (consent ~ 15% of eligible participants; attrition rate < 30%). Acceptability, validated sustained abstinence and ≥ 50% cigarette consumption reduction at 1-month, were also evaluated and qualitative interviews conducted to further explore acceptability in this population. Results Feasibility targets were partially met; of 201 eligible participants, 43 (mean age = 45.2, SD = 12.7; 39.5% female) were recruited (21.4%) and randomised (intervention:48.8%, n = 21; control:51.2%, n = 22). Attrition rate was 37.2% at 1-month follow-up and was higher (45.5%) in the control group. At follow-up (n = 27), 93.3% (n = 14) in the intervention group and 25.0% (n = 3) in the control group reported e-cigarette use. The intervention was well received with minimal negative effects. In intention-to-treat analysis, validated sustained abstinence at 1-month was 2/21 (9.5%) and 0/22 (0%) and at least 50% reduction in cigarette consumption 13/21 (61.9%) and 3/22 (13.6%), for the intervention and control group, respectively. Qualitative analysis of participant interviews (N = 5) showed the intervention was broadly acceptable, but they also highlighted areas of improvements for the intervention and trial delivery. Conclusions Offering an e-cigarette starter kit to smokers with a mental health condition treated in the community was acceptable and largely feasible, with harm reduction outcomes (i.e. switching from cigarette smoking to e-cigarette use and substantial reduction in cigarette consumption) favouring the intervention. The findings of the study will be used to help inform the design of a main trial. Trial Registration Registry: ISRCTN. Registration number: ISRCTN17691451. Date of registration: 30/09/2021